MgAl Hydride Films for Enhanced Energy Conversion Efficiency of a Laser‐Driven Flyer. Issue 2 (23rd October 2020) - Wang, Liang; Ai, Mengting; Zhang, Wanli; Jiang, Hongchuan; Wang, Yao; Qin, Wenzhi; Zhang, Long; Ji, Xiangbo; Li, Yong; Tang, Duo
Abstract : Al, MgAl, and MgAl hydride films with an overall thickness of 1 μm are prepared by magnetron sputtering. Their surface morphology, structure, and heat properties are investigated using scanning electron microscopy (SEM), X‐ray diffraction (XRD), and laser flash method. XRD results confirm that hydrogen is successfully stored in the MgAl hydride films as MgH2 and Mg(AlH4 )2 are observed. Laser flash results show that the thermal diffusivity of MgAl hydride film is equivalent to MgAl film and much lower than Al film. Furthermore, these films are irradiated by pulsed lasers under 20.4, 30.6, 49.8, and 51 J cm −2, and their ability to launch 20 μm thick Al flyers is tested by measuring the flyer velocity using a photonic Doppler velocimetry. Results show that the velocity of Al flyers launched by MgAl hydride films is 1704 m s −1, 1816.8, 2451.6, and 2640 m s −1, respectively. The corresponding energy conversion efficiency is 38.5%, 29.1%, 39.8%, and 36.9%, respectively. Overall, there is a 30% and 140% increase in energy conversion efficiency for MgAl hydride films compared with MgAl and Al films. Therefore, MgAl hydride films serve as a good candidate for improving the energy conversion efficiency of a laser‐driven flyer. Abstract : The Al flyer velocity driven by MgAl hydrides is about 1.15 times of that for MgAl films and 1.5 times for Al films, indicating the energy conversion efficiency can be significantly improved by MgAl hydrides. To the best knowledge, this work presents for the first time metal hydrides are a new class of material with superior performance for laser‐driven flyers.